Failure of Ashraf Ghani’s Rapprochement Policy towards Pakistan (2014-2020): An Anatomization in Neoclassical Realist Perspective - Azhar Waqar; Muhammad Saeed Uzzaman; Javed Hassan Hashmi, (ASIAN Journal of International Peace & Security (AJIPS), 2021)
The article aims to critically evaluate President Ashraf Ghani's rapprochement policy by assessing its impact on Pak-Afghan bilateral ties and outlining the influencing factors that led to its failure. The failure of Ghani's rapprochement policy is examined comprehensively through the lens of neoclassical realism. The article is based on the qualitative nature of data and relies upon the integrative review. It is found that despite Ghani’s rapprochement towards Pakistan; the bilateral relations between the two states were challenged by plethora of quagmires. The domestic level of analysis proposes that internal schisms, weak institutions, multi-ethnic groups, and power struggles influenced the respective leadership's decision making as well as policy praxis. The international level of analysis emphasizes the importance of the US role and explicitly rules out Ghani's rapprochement policy. As a result, domestic factors as well as the anarchical structure played a significant role in stifling the rapprochement policy. According to the study, while acknowledging the existence of anarchy, Pakistan and Afghanistan must accommodate each other's national interests and capitalize on their geographical proximity for greater economic benefits.